(untitled) (Scientific journal of the Fergana State University, 2024)
The essence of the lexical unit is defined in the article through its inner side - sememe, and accordingly, through its relationship with other language units. The goal is to determine the grammatical meanings of the lexical units referring to the presupposition, which is one of the main objects of pragmatics, in the sentence, to reveal the laws of their reference to the presupposition, and to determine the reasons for the content complexity of simple sentences made with their participation. Also, the views of linguists about presupposition are given based on scientific analysis.